Achieving Health Goals in India: The Role of Community Engagement and Communication - Singh, Vishal (UI Scholars Hub, 2021)
India is committed to achieving the Sustainable Development Goals (SDGs) set up by United Nations. Community engagement (CE) and communicating health is the key aspect for achieving the desired results. Goal setting for health sector in India has long history. This systematic review aims to examine the evidence on community engagement and communication from studies that report on program outcomes in India. To our knowledge, there are limited reviews available that examine outcomes of CE in achieving health goals. This review seeks to fill this knowledge gap. We describe role of CE and communication in achieving the SDG health goals in India. The lessons learned this review may be useful in any developing country setting and may be utilized for planning and implementation for achieving the SDG by 2030. As methodology a systematic and realistic review of literature and Meta analysis is involved in this review paper. The review of literature includes program reports, documents, guidelines, research papers. Nationwide public health strategy, process of developing public health structures and achievements helping in improving status of health in India. Increasing capacity of the health care system, availability of trained human resources, efforts to improve the health care expenditure, and positive changes in demographic indicators shows that India is moving in right direction towards achieving SDGs. Based on various research and findings it has been derived that Engaging Community and adopting strategic path of communication can help in achieving the goals of SDG particularly in health sector in India.